Money-output granger non causality in a small open economy : Malaysian experience - Abdul Rahman, Kamaludin (2000)
The monetary expansion policy together with policy responses to development by the authorities to a much greater extent during the period of study (1976-1996) have resulted the causality running from money to output. Since we find that Ml has strongly influenced output, it is suggests that the authorities may use Ml as intermediate target for output growth without giving much pressure on price in the long-run. We also find that Ml is suitable intermediate target for maintaining price stability to curb inflation in the long-run. Strong Ml causal linkages on output is consistent with the huge amount of non performing loans and large inflows of FDI in Malaysia which both finally created excessive demand for money in the period of study. In the case of M2, it does not have any causal linkages with output as this findings support the monetary neutrality theory where M2 is found to be neutral in the long-run. From this study we conclude that monetary targeting is still a relevant policy amid the fast changing world, however, there must be in harmony with other policy (e.g. trade, fiscal and exchange rate policy) to achieve sustainable economic growth with price stability and external equilibrium.